Situación socioeconómica, desnutrición, anemia, deficiencia de hierro y parasitismo en niños que pertenecen al programa de complementación alimentaria alianza MANA-ICBF. Antioquia 2006 (2007)
ABSTRACT: to analyze the socio-economic situation, nutritional status by using anthropometrical measures, iron blood levels and parasitic disease in children who participate in the nutritional program: MANA-ICBF in Antioquia (Colombia). Methods: cross-sectional study. Representative and randomized sample was evaluated (n=2.759). Nutritional status was assessed: malnutrition z-score <-2 according to the NCHS reference, hemoglobin by Azida-Metahemoglobina technique, serum ferritin levels by natural quimioluminicense, parasites by direct coprology and concentration. Results: 14% of the children presented stunting (height-for-age), (CI; 95%:12,7-15,3), 8,0% low weight (CI; 95%:7,1-9,1), 1,9% wasting (Weight-for-height) (CI;95%:1,4-2,4). 6,4% had anemia (IC; 95%:5,5-7,3), 16,3% iron deficiency (IC; 95%:14,9-17,2). El 70,7% of the children had parasites (CI; 95%:68,7-72,7), 33,5% were infected with pathogenic parasites (CI; 95%:31,4-35,6) and 27,8% had multi parasites (CI; 95%: 25,9-29,7%). Conclusion: taking into consideration the socio-economic Colombian context children participating in the nutritional program had not a deteriorated nutritional status measured by anthropometrical indicators. Anemia prevalence was low, but children had Iron deficiency and the prevalence of parasitic disease in the population studied is high because of the insufficient sanitary conditions.